Respuesta :
All you have to do is plug and solve...
2(q+2) + 3q = -26
2q + 4 + 3q = -26
Subtract 4 from the left side and move it to the right...
2q + 4 + 3q = -26
- 4 - 04
_________________
2q + 3q = -30
Now add 3q and 2q together and you get 5q, next divide...
5q = -30
_______
5 5
Finally, you get q equal to negative 6 (-6)!
2(q+2) + 3q = -26
2q + 4 + 3q = -26
Subtract 4 from the left side and move it to the right...
2q + 4 + 3q = -26
- 4 - 04
_________________
2q + 3q = -30
Now add 3q and 2q together and you get 5q, next divide...
5q = -30
_______
5 5
Finally, you get q equal to negative 6 (-6)!
p=q+2 making 2p+3q=-26 become:
2(q+2)+3q=-26 perform indicated multiplication on left side
2q+4+3q=-26 combine like terms on left side
5q+4=-26 subtract 4 from both sides
5q=-30 divide both sides by 5
q=-6, and from earlier we know that p=q+2 so
p=-4
Thus (p,q)=(-4,-6)
2(q+2)+3q=-26 perform indicated multiplication on left side
2q+4+3q=-26 combine like terms on left side
5q+4=-26 subtract 4 from both sides
5q=-30 divide both sides by 5
q=-6, and from earlier we know that p=q+2 so
p=-4
Thus (p,q)=(-4,-6)